Errors in Conveyor Belt Weigher Systems - A. E. Hidden (Measurement + Control, 1973)
The necessity for continuous belt weighers is first discussed. It is pointed out that they have limitations in performance which at present prevent their widest adoption and which thus make their further study important. It is shown that conveyor belt weigher systems consist of four essential elements. These elements are each considered in turn and it is concluded that the most serious errors arise in the weigh-length element, with the means by which travel of the belt is measured as a possible further source of serious error. The weigh-length element is considered in further detail and the importance of multiple weighing idlers, long idler pitch, and low belt tension, amongst other things, is emphasised. The introduction of belt sag, instead of belt tension, as a term in equations for misalignment and tension errors is shown to give a convenient result. The effect of belt stiffness on the misalignment and tension errors is examined closely. Previous formulae for this are critically examined and the author presents the results of his own efforts to find a better formula. The difficulties of applying any of these formulae in practical cases is discussed. It is explained that simple beam theory is not applicable to a troughed belt, which, it is argued, should be found much more flexible than the beam theory predicts. Finally, the conclusion is reached that if belt sag, rather than belt tension, is taken as a criterion by which a belt weigher is adjusted, then a stiff belt should give rise to smaller misalignment and tension errors than a perfectly flexible one.